Informational and Methodological Support as a Factor of Continuous Professional Development of Pedagogues - Khujakulov Sherzod Amankulovich (International Journal on Integrated Education, 2022)
In the article, informational and methodological support is highlighted as a factor of providing consultative support and creating appropriate conditions in the process of continuous professional development of pedagogues. Also, the concept, content, essence, implementation forms, types and possibilities of informational and methodical support were discussed.